Relative tectonic activity assessment of the Northern Sumatran Fault using geomorphic indices - Putra, Aldo Febriansyah; Chenrai, Piyaphong (Frontiers in Earth Science, 2022)
Geomorphic indices have widely been applied to assess relative tectonic activity. The relative tectonic activity is mainly associated with relative uplift and long-term tectonic deformation. By considering this, the strike-slip basins along the Northern Sumatran Fault become suitable locations for the assessment. This study aims to evaluate the relative tectonic activity of the Northern Sumatran Fault with the focus on its strike-slip basins using geomorphic indices. This study utilized the Indonesian national digital elevation model (DEMNAS) with spatial resolution at 8.25-m. Here are the six geomorphic indices applied in this study along with the average values of the results: mountain front sinuosity (1.14–1.94), valley width-to-height ratio (0.58–1.93), stream length-gradient index (93.81–599.70), index of basin shape (1.66–3.16), asymmetric factor (7.45–19.93), and hypsometric integral (0.41–0.59). These results were used to generate the index of relative tectonic activity. The Northern Sumatran Fault exhibits, generally, alternating moderate and high tectonic activities and there is a northward decrease from very high to moderate tectonic activity in its northern part. The variation of relative tectonic activity of the fault coincides with the distribution of seismicity. This may suggest that the long-term tectonic deformation of the Northern Sumatran Fault has persisted to recent time.